La radio y la comprensión cultural: conocer las músicas Andinas de la contemporaneidad - Vega Seña, Marcos Fidel (Folios, revista de la Facultad de Comunicaciones y Filología, 2019)
The object of this study is a reflection on the way Colombian radio broadcasts the music of the Andes and how this problem has affected the level of understanding and acceptance of our own culture. Our objective is to analyse the role of radio in the popularization of Andean Colombian music. Thus, we have adopted a comprehensive method through the interpretation of surveys answered by the university population. The authors who write on the comprehension of culture and the dynamics of communication shed some light in this path for comprehension: Paul Ricoeur, Hannah Arendt, Jesús Martín Barbero, Zygmunt Bauman, Peter Wade, Carlos Miñana, Orlando Mora Patiño.